(untitled) (Research, Society and Development, 2022)
Objective: This study aims at reviewing the nursing role based on recent literature regarding patients submitted to cine coronary angiography, emphasizing arterial sheath removal procedure. Methods: This is an intuitive and narrative literature review, with a qualitative approach, using scientific articles published preferably in the last 5 years, available in full in Portuguese or English, in Scientific Electronic Library (Scielo), PubMED, and Biblioteca Virtual em Saúde (BVS) databases. Results: Nursing professionals provide complex and essential care for the maintenance of life in patients subjected to cine coronary angiography during every moment of their hospitalization. Brazilian nurses, when trained, have the autonomy and ability to proceed with arterial sheath removal after the percutaneous endovascular procedure in the catheterization laboratory. There are new vascular closure devices that can decrease hospitalization time in femoral punction cases. However, radial punction is still associated with a lesser adverse event rate. Evidence-based practices are key in preventing iatrogenics. Final considerations: There are several ways of removing the arterial sheath and reaching hemostasy. All of them require knowledge and experience in the best ways of providing nursing care and performing techniques, aiming for the patient to have the shortest possible recovery time, without increasing the risk to which he is subjected.